THE IMPACT OF DIGITAL PAYMENTS ON THE GROWTH OF CASHLESS PAYMENTS AND THE FACTORS LIMITING ACCESS TO FINANCIAL SERVICES - Zakir Zeynalov (Agora International Journal of Economical Sciences (AIJES), 2023)
Most countries worldwide are undergoing digitalization, with the adoption of non-cash payment methods accelerating. In recent years, the population and economic entities in our country have readily embraced the use of digital technologies. Organizing new methods of innovation is a key priority in the pursuit of strengthening the financial stability of the banking system. The introduction of new technologies serves as an effective tool for improving production potential, providing financial support, and stimulating entrepreneurship. Ensuring the reliability and security of the payment system, enhancing the efficiency and speed of payment operations, expanding financial inclusion by providing the population with access to payment services, minimizing the volume of cash circulation, and organizing and promoting new methods of innovation in the payment market. The application of financial technologies, especially in payment services, enables market participants to conduct their payments conveniently, safely, and at low cost. It allows for a broader involvement of economic cycles in the banking sector, limits the informal economy, and increases banks' credit resources and financial intermediation.
Keywords: 330